Ética de enfermería en la atención al paciente con trastornos psiquiátricos - Colcha Chacha, Erika Mishell (2025)
Nursing ethics is a cornerstone in the care of patients with psychiatric disorders, ensuring a humanized and respectful approach that allows nursing staff to act with sensitivity and empathy. This approach is vital in recognizing the emotional vulnerabilities of these patients and respecting their dignity and rights. The primary objective of this research was to analyze the importance of ethics in nursing care for patients with psychiatric disorders, with a specific focus on the role of bioethical principles. The study aimed to identify these principles that nursing staff should apply in caring for these patients and to classify care based on the four stages of Hildegard Peplau's interpersonal relationships theory. The methodology was based on a comprehensive bibliographic review, drawing information from various databases. A sample of 64 articles was used, and a discussion of the findings was conducted based on the triangulation of criteria. This process yielded the main care strategies based on the bioethical principles required by patients with psychiatric disorders in each of the phases according to Hildegard Peplau's theory. In conclusion, ethics is an essential pillar in ensuring humanized and respectful care, which includes applying beneficence, autonomy, justice, and non-maleficence to promote patients' integral well-being and recovery.